2021
DOI: 10.1021/acsami.1c02613
|View full text |Cite
|
Sign up to set email alerts
|

An Efficiency of 16.46% and a T80 Lifetime of Over 4000 h for the PM6:Y6 Inverted Organic Solar Cells Enabled by Surface Acid Treatment of the Zinc Oxide Electron Transporting Layer

Abstract: For the inverted organic solar cells (OSCs), the interface contacts between the ZnO electron transporting layer and the organic active layer play an important role in the device performance and stability. Since the solution-processed ZnO surface always contains some base or zinc salt contaminants, we explored how the surface pH conditions influence the performance and stability of the nonfullerene acceptor (NFA) cells. A tight relationship between the surface pH condition and the device performance and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 69 publications
6
108
0
1
Order By: Relevance
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 88%
“…This result unambiguously confirms that the 𝛽-side chains next to the C═C bond have great influence on the stability of the NFA molecules and the corresponding device performance. Our previous finding showed that treating the ZnO surface with Lewis acid, such as 2-phenylethanethiol (PET), [25,27] can decrease the photon reactivity of ZnO film and consequently improve device stability. With this, a PSC with an inverted structure of ITO/ZnO (PET treated)/PM6:L8-BO/MoO 3 /Al was fabricated, which showed the highest PCE of 17.02% (inset in Figure 5e, see also Figure S7 and Table S3, Supporting Information, for more details).…”
Section: More Stable Nfa Molecule With Branched 𝜷-Alkyl Side Chainmentioning
confidence: 99%
“…[ 14 ] In addition to the intrinsic morphological changes in bulk heterojunction blends, [ 24 , 25 ] the changes in morphology, induced by the active layer/transporting layer interfaces, can also affect the cell performance over time. [ 26 , 27 ] This highlights the urgent need to understand the effects of internal changes in OPVs under environmental stresses and to prevent or minimize these changes. Some amine‐containing polymer electron transporting layers (ETLs), such as polyethylenimine (PEI), polyethylenimine ethoxylated (PEIE), and poly[(9,9‐bis(3 ′ ‐(N,N‐dimethylamino)propyl)‐2,7‐fluorene)‐alt‐2,7‐(9,9‐dioctylfluorene)] (PFN) have a tendency to react with the nonfullerene active layer, resulting in poor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Among the metal oxides, zinc oxide (ZnO) has been widely used as the ETLs in fullerene-based OSCs for its high transparency and good conductivity. [9] ZnO ETLs can be prepared by nanoparticle route [10] or sol-gel route. [11] Most recently, Hou et al developed a new method of printable ZnO as the ETL for flexible OSCs.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…ZnO ETLs prepared from nanoparticle methods or sol-gel methods often suffer from plentiful surface defects, which introduce a high density of recombination centers, leading to insufficient charge extraction and transport. [9] To passivate these defects, extensive efforts have been devoted to surface modification. Introducing an extra layer of organic electrolyte is a facile way to passivate the defects and improve the interfacial contact.…”
Section: Metal Oxidesmentioning
confidence: 99%